Guinea : Joint Bank-Fund Debt Sustainability Analysis, 2018 Update - International Development Association; International Monetary Fund (World Bank, Washington, DC, 2018)
The results of the update of the Debt Sustainability Analysis (DSA) show that Guinea continues to be at a moderate risk of external debt distress. All external debt burden indicators under the baseline scenario lie below their policy-dependent thresholds and debt dynamics have improved compared to the 2017 DSA, given higher-than-anticipated growth during 2016–17. Stress tests suggest that debt vulnerabilities owing to accumulation of external debt related to financing of infrastructure projects will increase if adverse shocks materialize, though remaining more contained than in the 2017 DSA. Under most extreme stress tests, all solvency and liquidity indicators except one breach their thresholds and for prolonged periods. The inclusion of domestic debt does not significantly change the conclusion of the external DSA. A prudent external borrowing strategy aimed at maximizing the concessionality of new debt, limiting non-concessional loans in line with programmed amounts, and strengthening debt management will be key to preserving medium-term debt sustainability.